2022
DOI: 10.3389/fcell.2022.934586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mutant lamins on nucleo-cytoskeletal coupling in Drosophila models of LMNA muscular dystrophy

Abstract: The nuclei of multinucleated skeletal muscles experience substantial external force during development and muscle contraction. Protection from such forces is partly provided by lamins, intermediate filaments that form a scaffold lining the inner nuclear membrane. Lamins play a myriad of roles, including maintenance of nuclear shape and stability, mediation of nuclear mechanoresponses, and nucleo-cytoskeletal coupling. Herein, we investigate how disease-causing mutant lamins alter myonuclear properties in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 130 publications
0
9
0
Order By: Relevance
“…Alternatively, human laminopathies that affect both skeletal and cardiac muscle often have dysmorphic nuclei, which are proposed to be the result of the extreme mechanical forces these nuclei are subject to [81][82][83]. A third possibility is that nuclear deformation could result from altered nucleocyto-skeletal coupling in lmn-1 missense variants, similar to what has been reported in other laminopathy models [30,84,85].…”
Section: Table 1 Phenotypic Scoring Of C Elegans Laminopathy Modelsmentioning
confidence: 80%
“…Alternatively, human laminopathies that affect both skeletal and cardiac muscle often have dysmorphic nuclei, which are proposed to be the result of the extreme mechanical forces these nuclei are subject to [81][82][83]. A third possibility is that nuclear deformation could result from altered nucleocyto-skeletal coupling in lmn-1 missense variants, similar to what has been reported in other laminopathy models [30,84,85].…”
Section: Table 1 Phenotypic Scoring Of C Elegans Laminopathy Modelsmentioning
confidence: 80%
“…Early experiments showed that depletion of Lamin A/C softens nuclei and makes them more deformable. Furthermore, it has been reported that the expression of mutant Lamin C, which induces laminopathy, in Drosophila muscles can lead to mechanical stress-induced deformations in nuclear shape ( Shaw et al, 2022 ; Zwerger et al, 2013 ). These reports suggest that Lamins A and C are important contributors to the mechanical stiffness of nuclei ( Broers et al, 2004 ; Lammerding et al, 2004 , 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Lamin Dm0 null mutant larvae exhibit reduced locomotion, the absence or slight reduction in the size of LO1 muscle, and fine structure defects in fibrillar organization ( Muñoz-Alarcón et al, 2007 ). Moreover, expression of Drosophila N-terminal truncated Lamin C or mutations representing human Lamin A laminopathy mutations in larval wall muscle result in lethality, mislocalization of nuclear membrane proteins, nucleo-cytoskeletal uncoupling, and locomotion defects ( Coombs et al, 2021 ; Dialynas et al, 2010 , 2012 ; Schulze et al, 2009 ; Shaw et al, 2022 ; Zwerger et al, 2013 ). The fact that the phenotype is observed only in muscle upon PIGB deficiency may be related to the fact that even in laminopathies caused by lamin mutations, the tissues in which the pathology manifests itself differ depending on the type of mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila is a powerful organism for modeling human disease, including neuromuscular disorders [ 107 , 108 , 109 , 110 , 111 , 112 , 113 ]. Such models have provided novel insights into disease mechanisms and identified potential drug targets and treatments [ 64 , 113 , 114 , 115 , 116 , 117 , 118 ]. In addition, Drosophila is one of a few selected model organisms used by the Undiagnosed Disease Network (UDN) to functionally test DNA sequence variants of uncertain significance in candidate disease genes ( ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding in Drosophila , cytoplasmic NUPs are also observed in human muscle biopsy tissue from individuals with LMNA -associated muscular dystrophy [ 91 ], demonstrating clinical relevance. Given that some mutant lamins cause cytoplasmic nuclear pore distribution, whereas others do not, there might be different mechanisms of pathogenesis among individuals with skeletal muscle laminopathies [ 31 , 91 , 116 ].…”
Section: Discussionmentioning
confidence: 99%